Efecto de la incorporación de abonos verdes en el cultivo de maíz duro (zea mays l.), en la zona de Babahoyo - Pisco Acosta, José Omar (2017)
SUMMARY The objective of this investigation was to evaluate the effect of the incorporation of green payments in the cultivation of hard corn. Additionally he/she was carried out an economic analysis. The work was carried out in the properties of the Farm "San Pablo" of the UTB, located in Km 7, 5 via Babahoyo-Montalvo. Seven treatments and an absolute witness were investigated, with 3 repetitions. The crops was carried out with seeds of the hybrid clone of corn Pioneer 30K73, in parcels of 15 m2. The treatments were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to 5 % significance. Concluding the cultivation was evaluated: plant height, area will foliate effective, ear diameter, ear longitude, weight of 100 grains, number of arrays for ear, ear number for plant, yield for hectare and economic analysis.. The results determined that the incorporation of green payments impacts substantially on the growth and development of the hybrid cultivation of corn. With Population's of Corn application T7 (62 500 pl/ha + Fertilization A.S), it increases the growth of plants of corn. Ears of more diameter of shafts are generated in the treatment T7 (Population of Corn of 62 500 pl/ha + Fertilization A.S). Also the ear number for plant spreads to be increased using the treatments T1 (Population 1 Corn 60 000 pl/ha + Density Leguminous Soy 30 kg/ha) and T7 (Population of Corn of 62 500 pl/ha + Fertilization A.S.). Bigger increment of grain yield was given incorporating to the floor the treatment T6 (Population 3 Corn 80 000 + Leguminous Density Soy 3 50 kg/ha) with 9046,7 kg/ha and T7 (Population of Corn of 62 500 pl/ha + Fertilization A.S) with 8827,3 kg/ha.